van Hiele Levels of Thinking Predict Students' Mathematics Grade - Purisima Yap (Philippine Association of Institutions for Research, Inc., 2014)
The van Hiele levels of thinking has five reasoning levels, namely, holistic, analytic, abstract, deductive, and rigorous. This study aimed to determine the effects of spatial activities to the students' van Hiele Levels of thinking. It evaluated the van Hiele levels of geometrical reasoning taking into account the van Hiele level they reflected and their mathematical accuracy after exposure to spatial activities. Pretest-posttest design was used in this study. Sixty third-year high school students from five sections were the subjects with 30 students each in the control and experimental groups. The results revealed that only Level 1 in the post-test was significant. As to the type of reply, the post-test results showed that the control group acquired low acquisition to high acquisition in each level while the experimental group had low acquisition to complete acquisition in each level. Only Level 2 in the control group and Levels 3 and 4 in the experimental group could predict Mathematics grade. The control group had weaker reasoning capabilities in answering geometry problems; while the experimental group increased their level of reasoning, and thus, were able to answer geometry problems. This study concludes that the exposure to spatial activities would enhance the levels of reasoning of the third-year students in the study of geometry.